2012
DOI: 10.1016/j.fsi.2012.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression analysis of two ROR-γ homologues (ROR-γa1 and ROR-γa2) in rainbow trout Oncorhynchus mykiss

Abstract: This paper describes the cloning and characterisation of two retinoid-related orphan receptor (ROR)-γ homologues (ROR-γa1 and -γa2) in rainbow trout (Oncorhynchus mykiss). The coding region predicted for both homologues consists of 1410 base pairs (bp), which translate into two 469 amino acid (aa) proteins. The trout ROR-γs revealed a high conservation of both DNA- and ligand-binding domains (functional regions of the nuclear receptor family), and shared a high homology to mammalian ROR-γt. A phylogenetic tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…In vitro studies using trout cell lines demonstrated that ROR-g is induced significantly by LPS and downregulated by the presence of Poly I:C and recombinant interferon (IFN)-g. In vivo studies demonstrated that its expression was significantly higher in vaccinated versus unvaccinated fishes following bacterial (Yersinia ruckeri) challenge, but it was downregulated after a viral (VHSV) infection. All the data suggest a potential role of trout ROR-g, a putative TH17 transcription factor, in protection against extracellular bacteria [353].…”
Section: Genetic Studies In Fish Skinmentioning
confidence: 86%
“…In vitro studies using trout cell lines demonstrated that ROR-g is induced significantly by LPS and downregulated by the presence of Poly I:C and recombinant interferon (IFN)-g. In vivo studies demonstrated that its expression was significantly higher in vaccinated versus unvaccinated fishes following bacterial (Yersinia ruckeri) challenge, but it was downregulated after a viral (VHSV) infection. All the data suggest a potential role of trout ROR-g, a putative TH17 transcription factor, in protection against extracellular bacteria [353].…”
Section: Genetic Studies In Fish Skinmentioning
confidence: 86%
“…In fish, ROR-g orthologues have been identified in zebrafish [143], grass carp [144] and rainbow trout [145], with two paralogues in each species. Phylogenetic tree analysis revealed that the two cyprinid RORg molecules from the same species form two groups, whilst the two trout RORgs group within a single clade, suggesting that the two cyprinid RORgs arose from the teleost-wide WGD event but that the trout paralogues arose from an additional WGD in salmonids.…”
Section: The Master Transcriptional Factor Rorgtmentioning
confidence: 99%
“…Mammalian RORgts are produced using an alternative promoter in the second intron of RORg genes, and are 21 amino acids shorter at the N-terminal. Multiple alignment of protein sequences and gene organization analysis suggests that the fish RORg is more similar to mammalian RORgt than to RORg [145].…”
Section: The Master Transcriptional Factor Rorgtmentioning
confidence: 99%
See 2 more Smart Citations